Analisis Kemiskinan di Indonesia - Hilma Sundusiyah; Dini Rahmayanti (Journal of Islamic Economy and Community Engagement, 2025)
The aim of this research is to analyze poverty factors in Indonesia. The data used is panel data with data from 34 provinces from 38 provinces in Indonesia. The type of data used is in the form of panel data, namely a combination of cross sections and time series over a period of 4 years 2019-2022. The method used is quantitative data consisting of the open unemployment rate, poverty rate and human development index. The research results showed that open unemployment rate had an insignificant positive effect on poverty levels and HDI could not moderate the effect of open unemployment levels on poverty in Indonesia.